Antitumor effects of concanavalin A and Sophora flavescens lectin in vitro and in vivo - Shi Zheng; Chen Jie; Li Chun-yang; An Na; Wang Zi-jie; Yang Shu-lin; Huang Kai-feng; Bao Jin-ku (Acta Pharmacologica Sinica, 2016)
Zheng SHI1, 2, #, Jie CHEN3, #, Chun-yang LI1, #, Na AN1, Zi-jie WANG1, Shu-lin YANG2, Kai-feng HUANG2, Jin-ku BAO1, * 1School of Life Sciences and Key Laboratory of Bio-resources and Eco-environment, Ministry of Education, Sichuan University, Chengdu 610064, China; 2School of Life Sciences, Guizhou Normal University, Guiyang 550001, China; 3Central Laboratory of Clinical Medicine, Sichuan Academy of Medical Science Sichuan Provincial People’s Hospital, Chengdu 610072, China Aim: Proteins with legume lectin domains are known to possess a wide range of biological functions. > Here, the antitumor effects of two representative legume lectins, concanavalin A (ConA) and Sophora flavescens lectin (SFL), on human breast carcinoma cells were investigated in vitro and in vivo. Methods: Human breast carcinoma MCF-7 cells and human normal mammary epithelial MCF-10A cells were examined. Cell viability was detected using WST-1 and CCK-8 assays. Cell apoptosis was analyzed with Hoechst 33258 staining. Cell cycle was investigated using flow cytometry. The expression of relevant proteins was measured using Western blotting. Breast carcinoma MCF-7 bearing nude mice were used to study the antitumor effects in vivo. The mice were injected with ConA (40 mg/kg, ip) and SFL (55 mg/kg, ip) daily for 14 d. Results: ConA and SFL inhibited the growth of MCF-7 cells in dose- and time-dependent manners (IC50 values were 15 and 20 μg/mL, respectively). Both ConA and SFL induced apoptotic morphology in MCF-7 cells without affecting MCF-10A cells. ConA and SFL dose-dependently increased the sub-G1 proportion in MCF-7 cells, while SFL also triggered the G2/M phase cell cycle arrest. Both ConA and SFL dose-dependently increased the activities of caspase-3 and caspase-9 and release of cytochrome c from mitochondria into cytoplasm, up-regulated Bax and Bid, and down-regulated Bcl-2 and Bcl-XL in MCF-7 cells. ConA reduced NF-κB, ERK, and JNK levels, and increased p53 and p21 levels, while SFL caused similar changes in NF-κB, ERK, p53, and p21 levels, but did not affect JNK expression. Administration of ConA and SFL significantly decreased the subcutaneous tumor mass volume and weight in MCF-7 bearing nude mice. Conclusion: ConA and SFL exert anti-tumor actions against human breast carcinoma MCF-7 cells both in vitro and in vivo. Keywords: legume lectin; concanavalin A; Sophora flavescens lectin; anticancer drug; breast carcinoma; MCF-7 cell; apoptosis, cell cycle; breast carcinoma xenograft nude mouse We are grateful to Dr JianLI (Ohio University) and Wen-wen LI (University College London) for providing constructive suggestions. This work was supported in part by the National Natural Science Foundation of China (No 81173093, 30970643, J1103518, 81373311, and 31300674) and the Special Program for Youth Science and the Technology Innovative Research Group of Sichuan Province, China (No 2011JTD0026). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail baojinku@scu.edu.cn Received 2013-07-15 Accepted 2013-09-18